Potential Pathogenicity of Candida Species Isolated from Oral Cavity of Patients with Diabetes Mellitus. (27th May 2021) - Nouraei, Hasti; Jahromi, Mehdi Ghaderian; Jahromi, Leila Razeghian; Zomorodian, Kamiar; Pakshir, Keyvan
Abstract : Introduction . In the recent decade, the increased immunocompromised population such as diabetic patients makes a high incidence of invasive Candida infections. Diabetes mellitus is the most common endocrine metabolic disorder, and diabetic patients are more susceptible to oral candidiasis infection. Candidiasis is an opportunistic fungal infection caused by many species of Candida . Secretion of exoenzymes plays an important role in the virulence and pathogenesis of Candida species. The aim of this study was to evaluate the potential role of phospholipase, esterase, and hemolytic activity of Candida species isolated from oral cavity lesions of diabetic patients. Methods . A total of 108 Candida species including 75 Candida albicans and 33 non- Candida albicans species were recovered from the oral cavity of diabetic patients included in our study. Egg yolk agar, Tween 80 opacity medium, and blood agar plate assays were used for determining phospholipase, esterase, and hemolytic activities, respectively. Results . Candida albicans species had the most exoenzyme activity in comparison to non -albicans isolates. Candida albicans isolates showed 97.3%, 100%, and 77.3% phospholipase, hemolysin, and esterase activities, respectively. The difference between Candida albicans and non- Candida albicans was significant in phospholipase (P < 0.001 ) and hemolytic activity (P = 0.027 ), but not significant in esterase activity (P = 0.076 ). Conclusion . This study showed that most of the isolates had different enzymatic patterns, and Candida albicans isolates had the most exoenzyme activity. So due to the potential effects of these enzymes in pathogenesis and virulence effects of Candida species, we can conclude that the severity of extracellular enzymes may play a role in the severity of signs and symptoms of Candida oral cavity infections in diabetic patients.